2020
DOI: 10.1039/c9dt04252k
|View full text |Cite
|
Sign up to set email alerts
|

Unsymmetrical β-functionalized ‘push–pull’ porphyrins: synthesis and photophysical, electrochemical and nonlinear optical properties

Abstract: A new family of unsymmetrical β-TPA appended ‘push–pull’ porphyrins has been synthesized in good yield for the first time. They exhibited red shifted broad absorption spectral features with high dipole moments and tunable redox properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 77 publications
3
39
0
Order By: Relevance
“…Our group has recently reported the NLO properties of two unsymmetrically substituted novel porphycenes, i.e., 2,7,12,13-tetraethyl-9,10,19,20-tetramethyl(OAPo-T) and 2,3,16,17-tetraethyl-9,10,19,20-tetramethyl (OAPo-C) porphycenes with TPA cross-sections of 159 and 145 GM, respectively, obtained with exact experimental conditions (kHz, fs pulses at 800 nm) used in the present study. Similarly, one of our earlier works ( Rathi et al, 2020 ) reported fs, MHz NLO data of novel porphyrins [H 2 TPP(TPA) 2 NO 2 , H 2 TPP(TPA) 2 CHO, ZnTPP(TPA) 2 NO 2 , and ZnTPP(TPA) 2 CHO]. The obtained β values were ∼10 −8 cm/W, σ TPA values of ∼10 5 GM, n 2 values of ∼10 −13 cm 2 /W, and χ (3) values of ∼10 −11 e.s.u.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…Our group has recently reported the NLO properties of two unsymmetrically substituted novel porphycenes, i.e., 2,7,12,13-tetraethyl-9,10,19,20-tetramethyl(OAPo-T) and 2,3,16,17-tetraethyl-9,10,19,20-tetramethyl (OAPo-C) porphycenes with TPA cross-sections of 159 and 145 GM, respectively, obtained with exact experimental conditions (kHz, fs pulses at 800 nm) used in the present study. Similarly, one of our earlier works ( Rathi et al, 2020 ) reported fs, MHz NLO data of novel porphyrins [H 2 TPP(TPA) 2 NO 2 , H 2 TPP(TPA) 2 CHO, ZnTPP(TPA) 2 NO 2 , and ZnTPP(TPA) 2 CHO]. The obtained β values were ∼10 −8 cm/W, σ TPA values of ∼10 5 GM, n 2 values of ∼10 −13 cm 2 /W, and χ (3) values of ∼10 −11 e.s.u.…”
Section: Resultssupporting
confidence: 64%
“…Our group has recently reported the NLO properties of two unsymmetrically substituted novel porphycenes, i.e., 2,7,12,10,19, and 2, 3,16,10,19, porphycenes with TPA crosssections of 159 and 145 GM, respectively, obtained with exact experimental conditions (kHz, fs pulses at 800 nm) used in the present study. Similarly, one of our earlier works (Rathi et al, 2020) (3) values of ∼10 −11 e.s.u. for those molecules.…”
Section: Nonlinear Optical Measurementssupporting
confidence: 78%
See 2 more Smart Citations
“…The possibility of various types of chemical modification of these macrocycles at the periphery and in the coordination center resulting in the formation of strong metal complexes allows us to classify them as excellent preparations for photodynamic cancer therapy, electro-and photocatalysts for reduction and oxidation, light energy converters, materials with nonlinear optical properties, organic semiconductors and liquid crystals. [1][2][3][4][5][6][7][8][9][10] Porphyrin derivatives, acting as dyes and catalysts, play a vitally important role in a variety of processes, such as photosynthesis, breathing, and cell metabolism. [11][12][13][14][15] A lot of methods have been developed for porphyrin modification to change their physico-chemical properties.…”
Section: Introductionmentioning
confidence: 99%